O037 Understanding ventilatory control in children with Prader-Willi syndrome. (9th November 2022) - Patoglu, O; Davey, M; Nixon, G; Edwards, B; Horne, R
Abstract: Background: Children with Prader-Willi syndrome (PWS) are at risk of both central and obstructive sleep apnoea (OSA), and have abnormal respiratory control during wakefulness. Many children with PWS are treated with growth hormone (GH) however, GH has been associated with the development of OSA. In this pilot study, we aimed to determine whether sleep and respiratory control (i.e. loop gain, LG) characteristics were altered by GH in children with PWS. Methods: Pre- and post-GH polysomnographic data in children (aged 0-18 years) were retrospectively collected. LG was quantified in periods of NREM sleep by fitting a model of ventilatory control to the respiratory pattern following spontaneous sighs. Results: Results (n=15, range 5-134 months, 46.7%F) were compared pre- and post-GH. No significant differences in total sleep time (474 [447, 498] vs 475 [451, 495.5]; p=0.81), percentage time in NREM and REM sleep, the obstructive apnoea-hypopnoea (OAHI) index (0.0 [0.0, 0.4] vs 0.3 [0.0, 0.7]; p=0.15) or the central apnoea-hypopnoea index (CAHI) (3.0 [0.7, 6.3] vs 2.8 [1.4, 4.6]; p=0.63) were found however, 1 child developed OSA. GH had no impact on LG (0.4 ± 0.1 vs 0.4 ± 0.1; p=0.99) and the change in OAHI/CAHI showed no correlation with the change in LG. Conclusions: In this small cohort of children, the administration of GH had no impact on sleep and respiratory characteristics (including LG). A larger sample size maybe required to gain a more comprehensive understanding of the impacts of GH on ventilatory control in children with PWS.